Umbra e o caçador de androides: uma análise das relações ecológicas e tecnológicas na literatura distópica - LIMA, Amanda Oliveira (2019)
This study aims to analyze the dystopic narratives Umbra (1977), by Plínio Cabrale, and O Caçador de Androides (1968), by Philip K. Dick, using the studies of Ecocriticism and Ecofeminism and also of the Humanistic Geography and perspective of place. Aiming to achieve this objective, the presence of the nature in the aforementioned works and the way such presence is described are both analyzed, emphasizing, above all, an item which is mutual to both narratives: the destruction of the environment. Based on the ideas of ecology, feminism, and socialism, the basic premise of ecofeminism is that the ideology which authorizes oppressions, such as the ones based on race, class, gender, sexuality, physical abilities, and species, is the same ideology which sanctions the oppression of the nature (GAARD, 1993). The similarity between woman and nature lies in the fact that both are generators of life and in the exploration through which they are put throughout history. Plínio Cabral and Dick’s dystopias are based on man’s subversive and unruly action towards nature, while the society described on the works suffers with the consequences of its actions. The narratives on hand, thus, cause discomfort and stimulate reflection. Aiming to provide a discussion on this study, we will mention critics of science fiction and dystopia, such as Marek Oziewicz (2017), Adriana Amaral (2008), and Marceli Giglioli Stoppa Baldessin (2006); theorists of ecofeminism, such as Greta Gaard (1993), Ivone Gebara (1997), Laura Hobgood-oster (2002), besides scholars of humanistic geography, such as Werther Holzer (1998), Edward Relph (2014), and Alexandre Samir Rocha (2007). The results achieved with the presented work suggest a major contribution of the dystopic literature as a way that is capable of dialoguing with many areas of study, facilitating reflections both important and necessary to the social environment.